The Principal's Strategy in Creating an Environmentally Friendly School as a Model of Sustainable Character Education at SDN Sukarapih 03 Bekasi - Abdul Muklis; Suwito Eko Pramono; Nina Oktarina; Widiyanto; Arief Yulianto; Fathur Rokhman (Educational Management, 2026)
Sustainable character education is an important aspect in developing students who are disciplined, responsible, and environmentally conscious. This study aims to analyze the principal's strategy in realizing an environmentally friendly school as a model for sustainable character education at SDN Sukarapih 03 Bekasi. The study used a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman model with triangulation to ensure data validity. The results of the study indicate that the principal's strategy is implemented through the Planning, Organizing, Actuating, and Controlling (POAC) management function. Planning is carried out through the integration of environmental programs into school policies, organizing through collaboration with various stakeholders, implementation through habituation, role models, and environment-based learning, and supervision through continuous monitoring and evaluation. The research findings indicate that environmentally friendly schools function as an educational ecosystem that supports the formation of discipline, responsibility, and environmental awareness. The novelty of the study lies in the integration of the POAC management function with Bronfenbrenner's Bioecological Theory in explaining sustainable character formation through environmentally friendly schools.